A Novel Tandem Zinc Finger Protein in Gossypium hirsutum, GhTZF2, Interacts with GhMORF8 to Regulate Cotton Fiber Cell Development - Yang Li; Wei Xi; Jianfeng Hao; Li Zhang; Xingpeng Wen; Zhiguo Wu; Yuxian Zhu (Agronomy, 2023)
Arginine-rich Tandem Zinc Finger (RR-TZF) proteins make up a plant-specific superfamily that participates in plant development, while their roles in cotton fiber development remain to be explored. In this study, we identified an RR-TZF protein-coding gene, GhTZF2, containing two CCCH domains (C-X7-C-X5-C-X3-H-X16-C-X5-C-X4-C-X3-H) and one RR domain at the N-terminus of the two CCCH domains, by comparing the differences of chromatin H3K4me3 modifications between wild-type upland cotton (WT) and the fuzzless-lintless mutant (fl) ovules. GhTZF2 was highly expressed in ovule cells near anthesis, and multiple experiments revealed that GhTZF2 could interact directly with GhMORF8. Homozygotic GhTZF2-knockout cotton lines produced significantly shorter fibers with thinner cell walls. Additionally, comparative transcriptome analysis confirmed that many differentially expressed transcripts contain adenine- and uridine-rich (AU-rich) elements (AREs) in their 3’ untranslated regions (UTR). Together, this study indicated that GhTZF2 may regulate cotton fiber cell development through interacting with GhMORF8, or may be involved in mRNA turnover.